2020
DOI: 10.3390/jcm9103221
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends in Hospital Admissions for Pulmonary Embolism in Spain from 2001 to 2018

Abstract: (1) Background: The aims of this study were to examine trends in the incidence, clinical characteristics, and in-hospital outcomes of patients hospitalized with pulmonary embolism in Spain and to identify factors associated with in-hospital mortality (IHM). (2) Methods: We included all patients who were hospitalized for pulmonary embolism between 2001 and 2018. Data were collected from the Spanish National Hospital Discharge Database. (3) Results: We identified 241,821 hospitalizations for pulmonary embolism d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…An epidemiological study carried out in our country, between 2001 and 2018 in patients who were hospitalized for VTE, has concluded that these patients are older, have greater comorbidity and a decrease in mortality. 4 , 5 …”
mentioning
confidence: 99%
See 4 more Smart Citations
“…An epidemiological study carried out in our country, between 2001 and 2018 in patients who were hospitalized for VTE, has concluded that these patients are older, have greater comorbidity and a decrease in mortality. 4 , 5 …”
mentioning
confidence: 99%
“…A significant increase in the number of comorbidities has been observed over time. 5 Hypertension, diabetes, obesity, cancer and chronic kidney disease have increased significantly over time, some of which are known risk factors for PE. 5 …”
mentioning
confidence: 99%
See 3 more Smart Citations